2013
DOI: 10.1063/1.4801796
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic and photocatalytic behaviors observed in Ca-doped BiFeO3 nanofibres

Abstract: Ca-doped BiFeO3 nanofibres have been fabricated by electrospinning method. Our results indicate that phase transition from space group R3c to C222 can be observed by the Ca doping. These BiFeO3 nanofibres show obvious room temperature ferromagnetic behaviors, and saturation magnetization can be enhanced with the Ca-doping concentration increasing, which could be correlated with the variation of the ratio of Fe2+/Fe3+ valence state. The BiFeO3 nanofibres show obvious photocatalytic performance and can be improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…After the calcination treatment, the BFO nanofibers ( figure 2(b)) maintain a fibrous shape but show reduced and uneven diameter (∼383 nm), the decomposition of PVP from the nanofiber is the reason for the reduction in dimension of annealed fibers. With the increase of Co 3+ doping amounts, the diameter becomes smaller (the mean diameters of BFCO-1 and BFCO-2 are ∼286 and ∼278 nm respectively ), this is owing to appropriate Co 3+ doping maybe inhibits the growth of BFO grain during the sintering process that is consistent with previous reports [27,28]. Figure 4 shows the XRD patterns of BFO, BFCO-1, and BFCO-2 nanofibers.…”
Section: Resultssupporting
confidence: 83%
“…After the calcination treatment, the BFO nanofibers ( figure 2(b)) maintain a fibrous shape but show reduced and uneven diameter (∼383 nm), the decomposition of PVP from the nanofiber is the reason for the reduction in dimension of annealed fibers. With the increase of Co 3+ doping amounts, the diameter becomes smaller (the mean diameters of BFCO-1 and BFCO-2 are ∼286 and ∼278 nm respectively ), this is owing to appropriate Co 3+ doping maybe inhibits the growth of BFO grain during the sintering process that is consistent with previous reports [27,28]. Figure 4 shows the XRD patterns of BFO, BFCO-1, and BFCO-2 nanofibers.…”
Section: Resultssupporting
confidence: 83%
“…At this moment, the moment of Mn can help strengthen the magnetization instead, together with the Fe valence state variation and Fe 2+ -O-Fe 3+ super exchange [12,[14][15][16] caused by Ca doping. Our previous work has shown saturation magnetization is positively correlated with the Ca content, [11] while combining with this work, we can infer that Mn should have dual effects, one will be restrained by Ca doping, that is perhaps charge effect, and the other, which is likely to be residual moment, will cooperate with Ca on property improvement.…”
Section: Resultssupporting
confidence: 71%
“…Mn co-doping might endowed these nanofibres enormous impact on the thermal property and structure. In fact, our previous study [11] showed that an annealing temperature of 660˚C or a little lower was ideal for singly doped BFO nanofibres. In this co-doping case, we had to reduce the sintering temperature to 580˚C to keep the nanofibre shapes unbroken, though Mn concentration was as little as 5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the canted magnetic moment rotates in a spiral direction and forms a spiral spin structure with a period of 62 nm which cancels out the net magnetization in the bulk [3,4]. There are several reports showing enhanced magnetism in BiFeO 3 by doping elements varying from rare earth [5][6][7][8][9] earth to transition metal series [10][11][12][13]. Several arguments are put forward to explain the enhanced magnetic behavior such as destruction of the spiral spin arrangement [5,6], the size dependent suppression of spiral spin structure [7], uncompensated spins at the surface of nanoparticles [8], ferromagnetic coupling between the rare earth and iron ions [9], and change in Fe O Fe bond angle etc.…”
Section: Introductionmentioning
confidence: 95%